KREATIVITAS TARI CENGKAHING KATRESNAN OLEH ALERIANA MAYANG DEWATI - Dewati, Aleriana Mayang; Rahmani, Dwi (Greget: Jurnal Kreativitas dan Studi Tari, 2022)
Cengkahing Katresnan is a dance work created by Aleriana Mayang Dewati in 2021. This dance is presented in a group format with a theme that reflects the values of Dewi Banowati's devotion to her husband, Duryudana. In this performance, Dewi Banowati is portrayed as a dedicated woman, even as she faces various conflicts and challenges in her role as the wife of a great leader. This piece symbolizes sacrifice, love, and loyalty, which are central to her story. To create this work, Aleriana employed Alma M. Hawkins' creative process theory, which consists of three main stages: exploration, improvisation, and composition. Exploration involves searching for initial ideas, drawn from history, culture, and personal experiences. The improvisation stage is carried out by developing free movements, unrestricted by specific structures, allowing for creative freedom. The final stage, composition, is the process of arranging movements into a complete dance form. In addition, the author utilized Maryono's form theory to analyze the structure and supporting elements within this dance piece. This theory aids in understanding how each movement, pattern, and placement of dancers on stage contribute to conveying the story and its meaning. The research found that Aleriana Mayang Dewati's creativity is influenced by both internal factors, such as her life experiences and artistic vision, and external factors, such as cultural environment and social support. This study also explores the various supporting components of the work, including music, costumes, and stage design, all of which play crucial roles in shaping the aesthetic experience for the audience.